Les désaccords éditoriaux dans Wikipédia comme tensions entre régimes épistémiques - Guillaume Carbou; Gilles Sahut (Communication)
Despite its highly normative architecture, Wikipedia is a place of recurrent disagreements between contributors. By analyzing the arguments in a corpus of discussion pages for articles on highly controversial subjects (genetically modified organisms, September 11, etc.), the authors show that these arguments are partly fed by the existence on Wikipedia of concurrent “epistemic regimes”. These epistemic regimes (encyclopedic, scientific, scientistic, wikipedist, critical, and doxic) correspond to divergent notions of validity and the accepted methods for producing valid information.